ChemInform Abstract: Cycloadditions to Epoxides Catalyzed by Group III—V Transition‐Metal Complexes. Issue 34 (August 2015) - D'Elia, Valerio; Pelletier, Jeremie D. A.; Basset, Jean‐Marie
Abstract Review: [63 refs.